Nanostructured Hybrids Based on Tantalum Bromide Octahedral Clusters and Graphene Oxide for Photocatalytic Hydrogen Evolution - Jhon Sebastián Hernández; Maxim Shamshurin; Marta Puche; Maxim N. Sokolov; Marta Feliz (Nanomaterials, 2022)
The generation of hydrogen (H2) using sunlight has become an essential energy alternative for decarbonization. The need for functional nanohybrid materials based on photo- and electroactive materials and accessible raw materials is high in the field of solar fuels. To reach this goal, single-step synthesis of Ta6Bri12@GO (GO = graphene oxide) nanohybrids was developed by immobilization of [Ta6Bri12Bra2(H2O)a4]·4H2O (i = inner and a = apical positions of the Ta6 octahedron) on GO nanosheets by taking the advantage of the easy ligand exchange of the apical cluster ligands with the oxygen functionalities of GO. The nanohybrids were characterized by spectroscopic, analytical, and morphological techniques. The hybrid formation enhances the yield of photocatalytic H2 from water with respect to their precursors and this is without the presence of precious metals. This enhancement is attributed to the optimal cluster loading onto the GO support and the crucial role of GO in the electron transfer from Ta6 clusters into GO sheets, thus suppressing the charge recombination. In view of the simplicity and versatility of the designed photocatalytic system, octahedral tantalum clusters are promising candidates to develop new and environmentally friendly photocatalysts for H2 evolution.